1999
DOI: 10.2337/diacare.22.9.1549
|View full text |Cite
|
Sign up to set email alerts
|

Primary nociceptive afferents mediate the blood flow dysfunction in non-glabrous (hairy) skin of type 2 diabetes: a new model for the pathogenesis of microvascular dysfunction.

Abstract: These data suggest that neurogenic nociceptor-mediated vasodilation is impaired in subjects with type 2 diabetes when endothelial and sympathetic function are relatively intact. Heat-induced vasodilation may be a specific test of small heat-sensitive C-fiber peripheral neurons and may be an integral part of the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 18 publications
2
55
0
4
Order By: Relevance
“…Impaired vasodilatory response to plantar pressure causing tissue ischemia is the common final pathway, according to various theories, of the development of diabetic foot ulcers (Boulton et al, 2000). Diabetic patients (with or without peripheral neuropathy) suffer from various forms of microvascular dysfunction, including abnormal vasomotion (Benbow et al, 1995;Stansberry et al, 1996;Bernardi et al, 1997), impaired vasodilatory response to local heating (Malik et al, 1993;Stansberry et al, 1999), decreased blood flow under or after pressure loading (Fromy et al, 2002;Koitka et al, 2004), endothelial nitric oxide dysfunction (Veves et al, 1998), and attenuated response to sympathetic maneuvers (Aso et al, 1997).…”
Section: Microvascular Factors and Ulcerationmentioning
confidence: 99%
“…Impaired vasodilatory response to plantar pressure causing tissue ischemia is the common final pathway, according to various theories, of the development of diabetic foot ulcers (Boulton et al, 2000). Diabetic patients (with or without peripheral neuropathy) suffer from various forms of microvascular dysfunction, including abnormal vasomotion (Benbow et al, 1995;Stansberry et al, 1996;Bernardi et al, 1997), impaired vasodilatory response to local heating (Malik et al, 1993;Stansberry et al, 1999), decreased blood flow under or after pressure loading (Fromy et al, 2002;Koitka et al, 2004), endothelial nitric oxide dysfunction (Veves et al, 1998), and attenuated response to sympathetic maneuvers (Aso et al, 1997).…”
Section: Microvascular Factors and Ulcerationmentioning
confidence: 99%
“…A variety of abnormalities have been described, including impairment in vasodilatory responses to skin heating, needle injury, postocclusive hyperemia, and response to ion-tophoresis of vasoactive substances (22)(23)(24)(25)(26)(27)(28)(29). Of particular interest is the finding of reduced maximal vasodilation to injury, including thermal (heating 44°C) and lacerating (needle prick) injury in people with diabetes (30,31).…”
mentioning
confidence: 99%
“…The ~35-min time delay between GA and GF under rapidly changing glucose concentrations observed by Jungheim and Koschinsky [29] may have been caused by the higher capillary circulation on the fingertip, which is 5-20 times higher than that at the forearm [32][33][34], thereby leading to a slower glucose dynamics. On the other hand, McGarraugh [35] compared GA and GF with and without rubbing the forearm, and found that when the forearm was rubbed, the comparison yielded a nearly ideal correlation between GA and GF in the rapidly changing hyperglycemia region.…”
Section: Discussionmentioning
confidence: 96%